2012
DOI: 10.1371/journal.pone.0047248
|View full text |Cite
|
Sign up to set email alerts
|

Prion Domain of Yeast Ure2 Protein Adopts a Completely Disordered Structure: A Solid-Support EPR Study

Abstract: Amyloid fibril formation is associated with a range of neurodegenerative diseases in humans, including Alzheimer’s, Parkinson’s, and prion diseases. In yeast, amyloid underlies several non-Mendelian phenotypes referred to as yeast prions. Mechanism of amyloid formation is critical for a complete understanding of the yeast prion phenomenon and human amyloid-related diseases. Ure2 protein is the basis of yeast prion [URE3]. The Ure2p prion domain is largely disordered. Residual structures, if any, in the disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The EPR spectra of spin-labeled A␤42 globulomers encode information about the mobility of the spin label at each labeling site. The spin label mobility can be measured using center line width (45) or the ratio of high field and center line amplitude (46). For EPR spectra with multiple components reflecting multiple motional states of the spin label, however, these measurements report only the combined mobility from different spin label states.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EPR spectra of spin-labeled A␤42 globulomers encode information about the mobility of the spin label at each labeling site. The spin label mobility can be measured using center line width (45) or the ratio of high field and center line amplitude (46). For EPR spectra with multiple components reflecting multiple motional states of the spin label, however, these measurements report only the combined mobility from different spin label states.…”
Section: Resultsmentioning
confidence: 99%
“…3B). Spin labels in completely unfolded proteins have a correlation time of ϳ0.5 ns (46,47), suggesting that this fast component corresponds to a partly disordered state. The relative population of the fast component is ϳ25% for N-terminal region (residues 1-10) and 10 -15% for most other residues ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…122 PrDs of prions that exhibit self assembly and aggregation are found to exist in disordered state and are also predicted to be IDRs/LC domains. [164][165][166] The biophysical nature and structural details of interaction between these domains in vivo remains to be clearly identified. Strikingly although only 1% of human genome contain RNA recognition motif (RRM), 11% of human prion domain containing proteins possess RRM, indicating their enrichment in the subset.…”
Section: Prion Like Domains In Neuronal Rnp Mediated Translationmentioning
confidence: 99%
“…Interestingly, it has been reported that Q was overrepresented in protein interaction domains [37]. It was recently reported that the Ure2p prion and other Q/N-rich yeast prion proteins, which were completely disordered, were driven to format amyloid primarily by intermolecular interactions [38]. Meanwhile, as shown in Figure 3(b), for the 21-length peptides, PSSM conservation scores at sites 8–15 played the most important role.…”
Section: Resultsmentioning
confidence: 94%